Vaccination protects against in vivo-grown feline immunodeficiency virus even in the absence of detectable neutralizing antibodies. - Matteucci, D (1996)
So far, vaccination experiments against feline immunodeficiency virus have used in vitro-grown virus to challenge the vaccinated hosts. In this study, cats were vaccinated with fixed feline immunodeficiency virus-infected cells and challenged with plasma obtained from cats infected with the homologous virus diluted to contain 10 cat 50% infectious doses. As judged by virus culture, PCRs, and serological analyses performed over an 18-month period after the challenge, all of the vaccinated cats were clearly protected. Interestingly, prior to challenge most vaccines lacked antibodies capable of neutralizing a fresh isolate of the homologous virus.